Hubungan Mekanisme Koping dan Kecemasan Pada Pasien Pra Endoskopi di Poliklinik Penyakit Dalam RSUD Raja Ahmad Thabib - Nurani Cipta Lestari; Mira Agusthia; Rachmawaty M. Noer (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Esophagogastroduodenoskopi procedure is an invasive procedure that can cause problems in patients who will undergo it. To overcome anxiety, a coping mechanism is needed. Purpose: This study aims to find out the relationship between coping mechanisms and anxiety levels of Pre Endoschopy patient in the internist unit at Raja Ahmad Thabib Public Hospital. The study method used a correlation analytic design with a cross sectional approach. The number of samples obtained by 32 respondents with the sampling technique used is total sampling. Statistical analysis using the Spearman Rho test with SPSS version 26. The results of this study showed there is a meaningful relationship between coping mechanisms and pre Endoschopy patient in the internist unit at Raja Ahmad Thabib Public Hospital (p =0.001) at signification values of 0.05 and r =- 0.734, indicating that the direction of negative correlation with the strength of strong relationships, so that it can be concluded the more adaptive the coping mechanism then the lower the anxiety level. conclusion The use of proper coping mechanisms in pre esophagogastroduodenos copy patients can lower anxiety level